Perbandingan Efisiensi Daya Penguat Audio Kelas AB dengan Penguat Audio Kelas D untuk Keperluan Sound System Lapangan - Kharis, Muhamad; Prastiyanto, Dhidik; Suryono, Suryono (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2018)
Class AB audio amplifiers are commonly used but the efficiency is 50%. While the efficiency of class D audio amplifiers is 90% but are rarely used. The purpose of this research is to know how much the power efficiency of field sound system between 1000 watts class AB amplifier and 900 watts class D amplifier. This study is a comparative study that compares different variables with the same sample. The results of power efficiency are obtained from the percentage comparison between the output power and the input power of each audio amplifier. The power efficiency of class D audio amplifiers with IRS D900 type larger than class AB audio amplifiers with Apex B500 type. The efficiency value of class D audio amplifiers at the highest output power reaches 87% while class AB audio amplifiers are only 73%.